Crop diversification for sustainable farming: What do farmers think? - Dubey, Swatantra Kumar; Veettil, Prakashan Chellattan; Deb, Proloy; Urfels, Anton; Kumar, Virender (CGIAR System Organization, 2024)
To shed light on farmers’ perspectives on crop diversification in India, and to identify the challenges encountered, NEXUS Gains conducted a series of focus group discussions across four districts of Haryana. Participants included 50 progressive farmers from the Yamuna Nagar, Karnal, Panipat, and Sonipat districts of Haryana Province.